2019
DOI: 10.26633/rpsp.2019.40
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de carne vermelha e processada, resistência insulínica e diabetes no Estudo Longitudinal de Saúde do Adulto (ELSA-Brasil)

Abstract: Objetivo. Investigar a associação entre consumo de carne vermelha e processada e a ocorrência de novos casos de resistência insulínica (RI) e diabetes mellitus (DM) em participantes do Estudo Longitudinal de Saúde do Adulto (ELSA-Brasil). Métodos. Estudo de coorte com 15 105 servidores públicos (idade: 35 a 74 anos). Dados bioquímicos, antropométricos, socioeconômicos e de estilo de vida foram coletados na linha de base (2008–2010) e na segunda onda (2012–2014). O consumo de carnes (g/dia) foi estimado por que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
2
0
5
Order By: Relevance
“…Notably, this significant association between red/processed meat consumption and DM has also been reported in other LMIC. In addition to Du et al's aforementioned study (17) , another investigation in Brazil found that red meat consumption was associated with a 40 % increase in the risk of DM (95 % CI = 1•04, 1•96) among men (26) . Even though red meat (particularly beef) is rich in oleic acid, which reportedly plays a role in countering insulin resistance (27) , our findings and those of others suggest that the increase in red meat consumption in LMIC may nevertheless be contributing to the rising prevalence of DM in these countries, where people have been experiencing rapid economic growth.…”
Section: Discussionmentioning
confidence: 80%
“…Notably, this significant association between red/processed meat consumption and DM has also been reported in other LMIC. In addition to Du et al's aforementioned study (17) , another investigation in Brazil found that red meat consumption was associated with a 40 % increase in the risk of DM (95 % CI = 1•04, 1•96) among men (26) . Even though red meat (particularly beef) is rich in oleic acid, which reportedly plays a role in countering insulin resistance (27) , our findings and those of others suggest that the increase in red meat consumption in LMIC may nevertheless be contributing to the rising prevalence of DM in these countries, where people have been experiencing rapid economic growth.…”
Section: Discussionmentioning
confidence: 80%
“…Participantes do sexo masculino e os mais jovens demonstraram ingerir maior quantidade de carnes do que as mulheres e os idosos, incluindo as carnes vermelhas e processadas, semelhante aos resultados de estudos nacionais e internacionais 13,14,17,24,[44][45][46] . Esses achados podem ter relação com a tendência das mulheres e dos idosos realizarem escolhas alimentares mais saudáveis, em decorrência da maior preocupação com a saúde 13 ou, no caso os idosos, da necessidade de controlar doenças crônicas mais comuns com o avançar da idade 44 .…”
Section: Discussionunclassified
“…Research, Society and Development, v. 10, n. 6, e45110615708, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i6.15708 (Aprelini et al, 2019). Já o consumo demasiado de gordura saturada está relacionado ao desenvolvimento de DCNT .…”
Section: Discussionunclassified
“…A obesidade abdominal constitui-se como um grande desafio a ser trabalhado pelos profissionais da saúde, gestores e formuladores de políticas públicas, considerando que uma fração significativa da população se encontra nessa circunstância (Aprelini et al, 2019). Nessa perspectiva, a prevenção e o controle da obesidade abdominal devem prover ações que auxiliem os indivíduos na adoção de estilo de vida saudável (Brasil, 2014).…”
Section: Discussionunclassified